Pengaruh Good Corporate Governance, Corporate Social Responsibility, dan Kinerja Keuangan Terhadap Nilai Perusahaan - Titik Eka Dewi Rahmawati; Erna Sulistyowati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine and explain the effect of good corporate governance, corporate social responsibility and financial performance on the firm value in the banking sector listed on the Indonesia Stock Exchange in 2020-2023. The population in this research is 47 banking sector companies listed on the Indonesian Stock Exchange in 2020-2023. Where the sampling technique uses purposive sampling technique with a total sample of 20 companies. This research uses a quantitative approach. The analysis and hypothesis testing technique in this research uses the Partial Least Square (PLS) analysis technique using SmartPLS. The research results show that Good Corporate Governance (GCG) has no effect on firm value, Corporate Social Responsibility (CSR) has no effect on firm value, financial performance has an effect on firm value.